MUTU KACANG TANAH RENDAH LEMAK YANG DIBERI BERBAGAI VARIASI PERLAKUAN PUPUK KANDANG DAN MULSA - Chitra Anggriani Salingkat; Amalia Noviyanty (Agroland: Jurnal Ilmu-ilmu Pertanian, 2019)
This study aimed to determine the effect of various treatments of mulch and manure on the quality of low fat peanuts. The research used a Two-factorial Completely Randomized Block Design with 16 treatments, each was replicated thrice. The first factor was various mulch rates consisting of with no mulch added, 2.5 t/ha mulch, 5.0 t/ha mulch and 7.5 t/ha mulch. The second factor was different manure rates i.e. with no manure added, 5 ton/ha manure added, 10 ton/ha manure added and 15 t/ha manure added. The interaction between the mulch and the manure significantly affected the quality of taste, flavor, color and likeness. The best peanut quality was found under the combination treatment of 7.5 t/ha mulch and 15 t/h manure which had oil reduction of 93.42%, moisture content of 4.56%, peanut skin percentage of 23.89%, and seed percentage of 76.10%.   Keywords : Fertilizer, Low Fat Peanut, Mulch, And Manure.